Investigation of risk factors associated with Ancylostoma spp. infection and the benzimidazole F167Y resistance marker polymorphism in dogs from the United States - Pablo D. Jimenez Castro; Jennifer L. Willcox; Haresh Rochani; Holly L. Richmond; Heather E. Martinez; Cecilia E. Lozoya; Christian Savard; Christian M. Leutenegger (International Journal for Parasitology: Drugs and Drug Resistance)
Ancylostoma caninum is the most significant intestinal nematode parasite of dogs. We acquired fecal surveillance data from a large population of dogs in the United States (US). A diagnostic test using real-time PCR (qPCR) for Ancylostoma spp. and allele-specific qPCR detecting the SNP F167Y in the isotype 1 of the Beta-tubulin gene, was used in 885,424 randomized canine fecal samples collected between March 2022 and December 2023. Overall, Ancylostoma spp. had a prevalence of 1.76% (15,537/885,424), with the highest in the South 3.73% (10,747/287,576), and the lowest in the West 0.45% (632/140,282). Within the subset of Ancylostoma spp.-detected dogs used for further analysis, the F167Y SNP had an overall prevalence of 14.44% with the highest in the West and the lowest in the Midwest (10.76%). The greyhound exhibited a higher prevalence of Ancylostoma spp. infections (17.03%) and a higher prevalence of the F167Y polymorphism (33.6%) compared to non-greyhounds (13.7% and 2.08%), respectively, but were not associated with the highest risk for the F167Y polymorphism. Sex did not influence hookworm infection nor F167Y polymorphism prevalence. Intact dogs had a prevalence of hookworm infection and F167Y polymorphism of 3.88% and 15.66%, respectively. Puppies showed increased prevalence of hookworms (3.70%) and the F167Y SNP (17.1%). Greyhounds, bluetick coonhounds, and boerboels had the highest relative risks for hookworm infection, while Cavalier King Charles spaniels, Havanese, and shiba inus had the lowest. The top and bottom three with the highest and lowest RR for the F167Y SNP were the old English sheepdog, American foxhound, and toy poodle Toy, and shih tzu, Maltese, and Australian cattle dogs, respectively. This study highlights the value of an accessible diagnostic qPCR test with fast turnaround in unraveling the molecular epidemiology of hookworms and benzimidazole resistance, as well as explore potentially important risk factorsin dogs with routine veterinary care.